Incidence of thrombocytopenia one month after initiation of heparin during hemodialysis: A n observational study - Krisnendu Das,; Utpal Bhui,; Arghya Majumdar,; Sanmoy Karmakar, (Indian Journal of Pharmacy & Drug Studies, 2024)
Thrombocytopenia, a platelet count below 150 × 109/L, may be acquired or congenital. In patients with chronic kidney disease on hemodialysis, thrombocytopenia may be multi-factorial. However, the most worrisome of these is heparin-induced thrombocytopenia (HIT), as it causes thrombosis in various vital organs in addition to bleeding. Heparin is the mainstay of anticoagulation on hemodialysis to prevent clotting in the extra-corporeal circuit. HIT may be either Type 1 (non-immune) or Type 2 (immune). The protocol of testing for the presence of thrombocytopenia 1 month after starting heparin on hemodialysis is seldom followed and the exact incidence of HIT in eastern India is unknown. We studied hemodialysis patients in a tertiary care hospital in Kolkata over a period of 9 months. All of them had platelet counts checked after starting hemodialysis as per protocol. No patients had symptoms or signs of HIT. A drop in platelet count was noticed in 3 patients, but it was transient and attributable to other causes. It did not necessitate stopping of heparin and the platelet count spontaneously improved. So, it is reassuring that HIT is rare in the eastern part of India.